The first prick counts: evaluating head and neck masses with fine needle aspiration cytology - Singh, Shivam; Bajoliya, Sunil; Sharma, Sweta; Mourya, Rituraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Cervical swellings are common clinical presentations with causes ranging from benign inflammatory conditions to malignant neoplasms. Fine needle aspiration cytology (FNAC) is a safe, rapid, minimally invasive, and cost-effective first-line diagnostic tool for their evaluation. The objective was to study the spectrum of head and neck swellings and assess the diagnostic utility of FNAC. Methods: This observational study was conducted at Government Medical College, Khandwa, from February 2024 to February 2025, and included 100 patients with palpable head and neck swellings. After informed consent, FNAC was performed under aseptic precautions. Smears were stained with Papanicolaou, Giemsa, and Hematoxylin and Eosin (H&E) stains and evaluated cytomorphologically. Results: Among 100 patients, 61% were females and 39% males (ratio 1.56:1), with a mean age of 35.5 years. Inflammatory lesions constituted 43%, benign lesions 46%, and malignant lesions 11%. Lymph node swellings (35%) were most common, predominantly tuberculous lymphadenitis (17%). Thyroid lesions formed 21%, chiefly colloid goiter. Salivary gland lesions comprised 14%, with pleomorphic adenoma as the most frequent. Malignancies (11 cases) included metastatic squamous cell carcinoma, lymphoma, and papillary thyroid carcinoma. Conclusions: FNAC is a reliable, rapid, and economical diagnostic modality for head and neck swellings. It provides high diagnostic accuracy in distinguishing inflammatory, benign, and malignant lesions, guiding appropriate management and reducing unnecessary surgical procedures, especially in resource-limited settings where tuberculosis is still prevalent.